Impact of Design Interventions in Nursing Home on Residents with Dementia, Their Families, and the Staff - (:unkn) unknown (My University, 2001)
The purpose of this study was to determine whether certain design interventions in a nursing home affected resident with dementia outcomes, family involvement and interaction, and staff perceptions of care delivery. The study was conducted in a nursing home. The study site included dining and bathing facilities that serve smaller groups of residents. The new design promised to contrast the medical orientation of the existing nursing home with a more residential environment. The study design involved a two-group pretest-posttest comparison in which a sample of residents who eventually were relocated to the newly designed wing of the facility (Treatment Group) was compared with a sample that remained in the existing setting (Control Group). Findings and implication of this study provide new knowledge integrating the diverse professional aspects that contribute to a responsive long-term care setting.